Effect of particulate matter exposure on patients with COPD and risk reduction through behavioural interventions: the protocol of a prospective panel study. Issue 11 (9th November 2020) - Park, Shinhee; Ra, Seung Won; Kang, Sung Yoon; Kim, Hwan-Cheol; Lee, Sei Won
Abstract : Introduction: Patients with chronic obstructive pulmonary disease (COPD) are vulnerable to particulate matter (PM) exposure which can increase acute exacerbations and hospitalisation. Interventions to avoid PM exposure are important but evidence-based guidance is lacking. This study aims to assess the impact of PM on lung function, quality of life and exacerbations in patients with COPD using a panel design study; it will also provide evidence for interventional measures to reduce harm from PM exposure. Methods and analysis: A prospective panel study of patients with COPD aged ≥40 years will be conducted. Patients will be required to have a forced expiratory volume in one second <80% of the predicted value at enrolment. A total of 120 patients from three different regions will be enrolled, 60 from the metropolitan area, 30 from an industrialised area and 30 from a clean rural area. Clinical outcomes will be assessed through COPD assessment test scores, the St. George's Respiratory Questionnaire for patients with COPD and pulmonary function testing. Indoor and outdoor PM in the patients' environments will be measured using gravimetric and light scattering platforms. To estimate the individual dose of PM exposure, a time–activity diary, Geographic Information System and land use regression model will be combined in every season for 1 year. The correlation between PM exposure and the health status of patients with COPD will be evaluated. In addition, 40 patients with the lowest score of life behaviour score to reduce environmental PM exposure will be randomised to a control or intervention group, who will receive in-depth education on risk-reducing behaviours. Ethics and dissemination: This study was approved by the Institutional Review Board of each site. The participants received comprehensive information and provided informed consent. The result of this study will be discussed in the form of conference presentations and peer-reviewed publications. Trial registration number: NCT04020237 .